Cloning and expression analysis of the murine lymphotoxin beta gene. - Pokholok, D K (1995)
Tumor necrosis factor alpha (TNF-alpha) and soluble lymphotoxin (LT) (also called LT-alpha or TNF-beta) are cytokines with similar biological activities that are encoded by related and closely linked genes. TNF-alpha, a mediator of the inflammatory response, exists in soluble and transmembrane forms. LT-alpha can be secreted or retained at the cell surface by binding to a 33-kDa transmembrane subunit, LT-beta. The recently cloned human LT-beta gene encodes another TNF family member and is linked to the TNF/LT locus within the major histocompatibility complex locus. The cell surface LT is a heterotrimer consisting of LT-alpha and LT-beta, whose physiological function is not yet clearly defined. We now report the sequence analysis of the genomic region and cDNA of murine LT-beta gene, which is closely associated with the TNF-alpha and LT-alpha genes within the murine major histocompatibility complex locus. Unlike the TNF-alpha, LT-alpha, and human LT-beta genes, which contain four exons, the murine LT-beta contains three exons and encodes a 244-amino acid polypeptide with a 66-amino acid insert that is absent from the human homologue. In situ hybridization demonstrates constitutive expression of LT-beta in lymphoid and hematopoietic tissues. LT-beta transcription is maximal in the thymic medulla and in splenic white pulp. LT-beta mRNA is also detected in the skin and in specific regions of the brain. The LT-beta promoter region contains putative Ets-binding sites, suggesting that the expression of LT-beta may be regulated in part by Ets transcription factors whose pattern of lymphoid expression overlaps that of LT-beta.